Grundtvig på anklagebænken. En redegørelse for hovedlinjer i de sidste ti års danske Grundtvig-reception og deres forhold til centrale motiver i Grundtvigs forfatterskab og dets virkningshistorie - Pedersen, Kim Arne (Grundtvig-Studier, 2002)
Grundtvig på anklagebænken [Grundtvig in the dock] By Kim Arne Pedersen The article opens with a review of Gr’s position after the second World War. The Heretica-era’s positive disposition towards religion and Christianity is inspired by the life-philosophy of Vilhelm Grønbech which in turn serves as a preliminary understanding of Gr’s thinking on the relationship between Christianity and folkelighed, the nourishing of a popular culture. Four significant currents have characterised Danish identity: Grundtvigianism, pietism, Brandes-influenced cultural radicalism and the social-democratic movement. Social-democratic thinking on social equality is examined in connection with the Grundtvigian-tendency’s elevation of the concept of folkelighed. With Reinhart Kosellek’s concept-historical methodology as aprompt, the Grundtvig-based concept offolkelighed is analysed in its association with the concept of liberty, ideas of social equilibrium, the question of a Constitution, and the concept of popular enlightenment (oplysning) in Gr’s authorship. The starting-point is an analysis of Gr’s ideas on Christianity andfolkelighed where it is pointed out that Gr, with his background in a Christian anthropology, emphasises their reciprocal bearing upon each other (vekselvirkning). The chief aim of the article is to demonstrate that the reception of Gr in the period 1883-1983 is characterised by a contest between, on the one hand, a philosophical interpretation of Gr which is linked with an understanding of the folkelighed-concept as an aspiration towards social equality and, on the other hand, a theological interpretation of Gr which concentrates upon humankind’s interaction with God in dialogue as the nub of Gr’s outlook on humankind. The article focuses upon the 1930s, when the social-democratic Education Minister Frederik Borgbjerg seizes upon the egalitarian aspect of Gr’s concept of folkelighed and uses it in the development of Social-Democracy into a national party. Borgberg’s interpretation of Gr embraces those components which characterise the following generation’s image of Gr: he is the supporter of liberty (and thereby tolerance), democracy and social equality, all as understood from their basis in the concept of folkelighed. Borgberg’s and Grønbech’s interpretations of Gr constitute the background to the understanding formed by Professor Hal Koch, church-historian and pillar of the folk-highschool system, of both Gr and the concept offolkelighed. But it is to be emphasised that Koch, in contrast to Borgberg and Grønbech, but in line with the author Jørgen Bukdahl, draws his understanding of the concept offolkelighed from the idea that the interaction between folkelighed and Christianity - that is, between the particular and the universal - is the underpinning perception in Gr’s writings. However, in the post-war period it is the thoughts of Pastor Kaj Thaning concerning the differentiation between Christianity and folkelighed which become dominant. Like Hal Koch, Thaning writes out of inspiration from the life-philosophy of Grønbech, but also like Koch he traces this back to its anchorage within Gr’s Christian universe. Thaning’s differentiation-thesis forms - against his own wishes – a starting-point for the 1970s convergence between the ideas of Gr and left-wing thinking on political emancipation, whereby the tendency from the 1930s now reaches its culmination: grounded in the construction of an adversarial relationship between Gr and grundtvigianism, and in a non-theological interpretation of Gr, the way is clear for Gr to become the leading figure in Danish national self-perception. In 1990 the literary historian and publicist Henning Fonsmark initiated the surge of criticism of Gr which from about 1992 has permeated the Danish public. With its starting-point in the debate over Denmark’s relationship to the European Union and over immigration into Denmark, one may observe a steadily more violent criticism of Gr among intellectuals who have a more or less loose connection to traditional cultural-radical milieus. At the same time the Danish immigration-opposed right wing, identifies itself with Gr - as in the case of the theological ‘Tidehverv’-movement, The Danish Association (Den Danske Forening) and The Danish National Party (Dansk Folkeparti). In contrast to the understanding of Gr hitherto prevailing, Gr is now widely interpreted as hostile to foreigners, intolerant, and the opponent of democracy and social equality. The viewpoint of the article is that both the right-wing use of Gr and the criticism of him are made possible only by an underestimation of his Christian premisses. When Gr’s Christian anthropology - and thereby the fellowship of dialogue between God and humankind - are appreciated as being the very core of his writings, then it becomes possible to maintain an image of Gr as the supporter of liberty, of social equality and of an enlightenment of and for life, which on the one hand appears as a consequence of modernity’s breakthrough in Western Europe and on the other takes its distinctive form from Gr’s understanding of Christianity as the bearer of that universality in whose light the particularity offolkelighed is to be understood. And it is this relationship which renders problematical a nationalistic reading of Gr’s authorship.